Detection and Identification of Mycobacterium tuberculosis Directly from Sputum Sediments by Ligase Chain Reaction - Moore, Douglas F. (American Society for Microbiology, 1998)
Sputum specimens received for the diagnosis of tuberculosis or other mycobacterial infections were tested by a ligase chain reaction (LCR)-based assay and acid-fast stain and culture techniques. Results from the LCR assay (Abbott LCx Mycobacterium tuberculosis [MTB] Assay) were compared to results from standard culture techniques held for 6 weeks. Four hundred ninety-three specimens from 205 patients suspected of pulmonary tuberculosis were included in the prospective study. Thirty-four (6.9%) of the specimens were culture positive for M. tuberculosis, and 13 (38%) of these were also fluorochrome stain positive. LCR sensitivities and specificities compared to culture were 74 and 98%, respectively. LCR sensitivity was 100% for fluorochrome stain-positive specimens and 57% for fluorochrome stain-negative specimens. Nine LCR-negative, culture-positive specimens were the result of low concentrations of M. tuberculosis. No inhibitors were detected in any of these specimens. Of the eight LCR-positive, culture-negative specimens, five were from patients with active tuberculosis. With these considered culture misses, final LCR sensitivity, specificity, positive predictive value, and negative predictive value were 77, 99, 91, and 98%, respectively. The same performance values for the fluorochrome acid-fast bacillus smear were 33, 98, 62, and 94%, respectively. After normal laboratory sputum processing, the Abbott LCx MTB Assay can be completed in 6 h. Thus, it is possible to have results available within 8 h of specimen submission.